Movie Stars in Politics: A Critical Analysis of Desmond Elliot’s Stewardship - Ramson Oloche Acheme; Steven Anu’ Adesemoye; E Timothy Ekeledirichukwu Onyejelem (Polit Journal Scientific Journal of Politics, 2025)
While contemporary movie stars are known as screen entertainers who enjoy massive popularity among young audiences, the audience often has high expectations of them. Viewers mostly see their screen heroes as ideal figures and assume the actors are the role they depict on the silver screen. This mental projection of thespians may be a mirage, as actors-turned-politicians seem not to meet the public expectations. Nollywood screen lover boy Desmond Elliot is among the few popular role interpreters who contested the 2015 elections and won the Surulere Constituency 1 seat in the Lagos State House of Assembly. Six years after his first electoral victory, Elliot remained a reference point for movie stars in Nigerian politics and many youths with popular and contending views of his public activities as a thespian-turned-politician. He became the poster boy for movie stars in politics. Subsequently, this study was initiated to ascertain the public perception of Desmond Elliot’s stewardship and movie stars in politics. The empirical result from this case would be used as a springboard to adjudge subsequent movie stars who showed interest in active politics. The study surveyed one hundred youths in Surulere Constituency 1, and the results were filed in simple frequency tables. Findings reveal that honourable Elliot scored a pass mark among his immediate constituents regarding political representation and the responds aver that they would vote for movie stars contesting popular vote. However, there was worry that most of the respondents who took part in this survey were staunch APC supporters. Therefore, it is recommended that this study be replicated in many areas to help ascertain the true perception of people regarding movie stars in politics. The credibility source theory was reviewed in this study.